Strengthening The Creative Economy Of The Community Through The Utilization Of Used Cooking Oil Waste Into Aromatherapy Candles - Rois Arifin; Agus Widarko; Mohamad Bastomi; Adelia Putri Pangestuti; Dewi Puspitasari; Muhammad Nur Alfandi (AKM, 2024)
Used cooking oil refers to the waste oil generated by households that has not been effectively utilized by the majority of individuals. The objective of this course on candle-making using waste cooking oil is to acquire valuable expertise in repurposing waste cooking oil. The produced candles can be utilized by individuals as a creative entrepreneurial venture or for personal use in their own homes. The method used in this activity is socialization and training by playing a video of the impact of continuous use of used cooking oil, followed by discussion and then practice. The target in the community service activity was the women of Pengajian Ngembul Hamlet. The results of the training and socialization of processing used cooking oil waste into economically valuable items such as aromatherapy candles make the product has its own selling value. The enthusiasm of the participants was very high and satisfied, apart from the fact that they had never thought about the benefits of cooking oil waste. The positive impact of this community service activity is that it can reduce waste cooking oil.